Insights into the cavitation behavior of a boundary layer pump - Bakogianni, Agapi; Rajendran, David John; Anselmi Palma, Eduardo; Pachidis, Vassilios; Palmer, Chloe Jo (American Society of Mechanical Engineers (ASME), 2025)
Several researchers in literature have claimed that boundary layer pumps have an increased resistance to cavitation because of the absence of blades. Their conclusion was obtained analytically by applying the simple assumption of uniform radial velocity at the entrance of all the channels. This study considers the effect of flow distribution between the channels and assesses the full 3D geometry of a boundary layer pump which was tested in an experimental campaign by Morris. The pump's flow field is obtained with steady-state multiphase 3D-RANS simulations in which the inlet total pressure is gradually reduced. For each inlet total pressure point, the vapor formation is examined, and hence the cavitation mechanisms are analyzed, and the head drop curve is obtained. Results show that the mass flow distribution in the channels is highly nonuniform, which heavily affects vapor formation areas. There is a 127% difference between the lowest and highest channel mass flow. Less mass flow is entering the channels closer to the entrance of the pump, because this requires the flow to turn almost 90 deg from the axial to the radial direction. The viscous forces accelerate less mass more easily, and this leads to up to 22% lower pressure values in the low flow channels. Therefore, vapor starts forming in these channels, and the further the net positive suction head (NPSH) reduces, it sequentially propagates to adjacent channels toward the back like a domino and expands its volume inside each gap.
Copyright VC 2025 by Rolls-Royce plc.
Keywords: 4012 Fluid Mechanics and Thermal Engineering; 40 Engineering; Energy; 4001 Aerospace engineering; 4004 Chemical engineering